Printing high performance reflective electrodes for organic solar cells - Krantz, Johannes; Forberich, Karen; Kubis, Peter; Machui, Florian; Min, Jie; Stubhan, Tobias; Brabec, Christoph (Organic Electronics, 2015)
In this paper we solve a long term material problem of thin film organic electronics, namely the solution processing of an opaque electrode. Solution processing of opaque metallic top electrodes typically leads to severe shunting problems. We solve this issue by reversing the electrode sequence and print a highly conductive but opaque bottom electrode from metallic precursors. Devices based on these printed bottom electrodes are compared to reference stacks based on evaporated silver. The transparent top electrode is solution processed from silver nanowire inks, which results in highly transparent electrodes with excellent conductivity. The optical, mainly reflective properties of the opaque silver electrode are investigated in comparison to screen-printed silver pastes. The outstanding smoothness of the printed Ag electrode results in high reflectivity and poly(3-hexylthiophene-2,5-diyl):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) based solar cells with η >. 2.5% and high fill factors performing on par with reference devices on evaporated silver electrode layers.
Keywords: Highly reflective electrode; Printed silver precursor ink; Solution processable electrode; Substrate architecture; Superstrate architecture